2011
DOI: 10.1155/2011/628670
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacology of Chemotherapy Agents in Older People with Cancer

Abstract: Populations around the world are aging, and the associated increase in cancer incidence has led to the recognition of the importance of geriatric oncology. Chronological age is a poor determinant of pharmacological response to cancer chemotherapy agents. Age-associated changes in physiology and organ function have a significant impact on the clinical pharmacology of cancer chemotherapy agents used in cancer treatment. Altered response to medicines in older people is a consequence of changes in body composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…With the changing demographics of an aging population, polypharmacy has become an increasingly pertinent issue in clinical practice [1][2][3][4][5][6] . In the literature, polypharmacy has been defined as the use of multiple drugs and of more drugs than clinically indicated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the changing demographics of an aging population, polypharmacy has become an increasingly pertinent issue in clinical practice [1][2][3][4][5][6] . In the literature, polypharmacy has been defined as the use of multiple drugs and of more drugs than clinically indicated.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, polypharmacy has been defined as the use of multiple drugs and of more drugs than clinically indicated. Despite the differences in definition, authors generally agree that the prevalence of polypharmacy has increased dramatically in recent decades and continues to increase [1][2][3][4][5][6] . Analyses of nationally representative surveys from the Swedish Panel Study of Living Conditions of the Oldest Old found that polypharmacy rates more than doubled to 46% in 2002 from 18% in 1992 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these requirements, early clinical indications for IL-2 excluded elderly patients, particularly those >70 years of age. Although older patients may exhibit differences in pharmacodynamics of cancer therapeutics based on alterations in organ function, frequent use of concomitant medications and the presence of other medical disorders, there is increasing evidence that elderly patients may tolerate cancer therapy, including surgical oncology procedures, radiation therapy and chemotherapy, as well as younger patients [8,9,10]. To date, there are no publications on outcomes of older patients treated with high-dose IL-2.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it should be noted that physiological changes related to aging and comorbidity can also increase the risk of toxicity of chemotherapy. 20 The use of antiemetics and analgesics prescribed by the doctor, teaching the skills needed to manage side effects (e.g. better oral hygiene and the use of warm compresses), as well as providing information to eat small meals or drink warm ginger drinks when nauseous, could be useful in decreasing the severity of their symptoms for the majority of this study's participants.…”
mentioning
confidence: 99%